Assessing the impact of mutual funds’ performance on investment decisions of fund managers in Ghana - AWUAH-SARPONG GLORY (knust, 2025)
A thesis submitted to the Department of Accounting and Finance, School of Business, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for theaward of the Degree of Master of Business Administration - Finance